Conversion of Goat Fibroblasts into Lineage‐Specific Cells Using a Direct Reprogramming Strategy. (15th September 2016) - Guo, Yanjie; Yu, Tong; Lei, Lei; Duan, Anqin; Ma, Xiaoling; Wang, Huayan
Abstract: Direct reprogramming is an efficient strategy to convert one cell type to another. In this study, due to the failure of maintaining the undifferentiated state of goat embryotic stem‐ and induced pluripotent stem‐like cells in vitro, we explored an alternative way to directly convert goat fibroblasts to lineage‐specific cells. The 'Yamanaka factors' was ectopically expressed in fibroblasts for a short term to situate cells in a metastable state. By culturing with lineage‐specific media for 1–2 weeks, the cardiomyocyte‐like cells and neurocyte‐like cells were generated and confirmed by the quantitative RT‐PCR and immunocytochemical staining. The metastable‐state cells could also be converted into oocyte‐like cells (OLCs) after culturing in media with retinoic acid (RA) and bovine follicular fluid (bFF) for 2–3 weeks. The generated OLCs were surrounded by cumulus granulosa cell‐like cells and formed a structure resembling goat cumulus‐oocyte complex from ovaries. This primary follicular structure could be developed further in oocyte mature medium and expressed germ cell‐specific markers. In addition, we found that the induction efficiency was higher and OLC cell size was bigger in bFF than in RA treatment. Altogether, the direct reprogramming of goat fibroblasts into lineage‐specific cells can facilitate stem cell research in domestic animals.